A pharmaceutical model for the molecular evolution of microbial natural products - David P. Fewer; Mikko Metsä‐Ketelä (Wiley-Blackwell, 2022)
Microbes are talented chemists with the ability to generate tremendously complex and diverse natural products which harbor potent biological activities. Natural products are produced using sets of specialized biosynthetic enzymes encoded by secondary metabolism pathways. Here, we present a two‐step evolutionary model to explain the diversification of biosynthetic pathways that account for the proliferation of these molecules. We argue that the appearance of natural product families has been a slow and infrequent process. The first step led to the original emergence of bioactive molecules and different classes of natural products. However, much of the chemical diversity observed today has resulted from the endless modification of the ancestral biosynthetic pathways. The second step rapidly modulates the pre‐existing biological activities to increase their potency and to adapt to changing environmental conditions. We highlight the importance of enzyme promiscuity in this process, as it facilitates both the incorporation of horizontally transferred genes into secondary metabolic pathways and the functional differentiation of proteins to catalyze novel chemistry. We provide examples where single point mutations or recombination events have been sufficient for new enzymatic activities to emerge. A unique feature in the evolution of microbial secondary metabolism is that gene duplication is not essential but offers opportunities to synthesize more complex metabolites. Microbial natural products are highly important for the pharmaceutical industry due to their unique bioactivities. Therefore, understanding the natural mechanisms leading to the formation of diverse metabolic pathways is vital for future attempts to utilize synthetic biology for the generation of novel molecules.